(untitled) (Research, Society and Development, 2020)
The Pedagogy of Alternation is a form of teaching organization where the spaces of formation intersperse between school and community. In this sense, we aim to analyze the narratives of the subjects investigated about their experiences about knowledge, experience and pedagogical knowledge. The study is a field research, with a qualitative approach. In obtaining data, we conducted the narrative interview with teachers-monitors of the “Casa Familiar Rural Vivendo a Esperança in São João do Sóter/ MA”. We took as theoretical support Pimenta (2005), Freire (2007), Tardif (2014), among others. It is noteworthy that 85.8% of the interlocutors have 5 (five) years or less experience time. It was evidenced that the subjects feel pleasure in sharing the knowledge with the students, knowledge that goes beyond the teaching of the contents. It is also possible to highlight that initial training allowed teachers to acquire knowledge that directly influences the way they develop their activities in the classroom. It is concluded that the interlocutors are possessed of savvy of knowledge, experience and pedagogical and act as teacher-monitors who value and respect the specificities of field education. This research brought reflections on the education of the field and teaching knowledge, opening possibilities for other researchers to be interested in the theme and to develop future studies.